Assessing the potential of small wind turbine electricity generation for small-sized hotels towards sustainable tourism in developing countries - Tanoto, Yusak; Jasman, Brandon Sebastian; Ananda, Stephanus Antonius (International Journal of Renewable Energy Development, 2025)
The persistent reliance on fossil fuels for energy will yield enduring adverse effects on the tourism sector, particularly the hotel industry. Wind energy represents a renewable electricity source that can facilitate the transition of small-scale hotels to clean energy. The main objective of this research is to propose a methodology for evaluating the potential of wind energy to support sustainable tourism in developing nations, specifically in fulfilling the electricity requirements of small hotels. This study aims to assess and compare the potential contribution of small wind turbines to hotel energy demand by modelling a historical hourly wind dataset spanning ten years (2011-2020) and forecasting a portion of the dataset. This research selected three sites in Indonesia exhibiting varying wind energy potentials: Tepus District in Gunung Kidul Regency, Losari Beach in Makassar City, and Nusa Penida Island in Bali. This study utilises multiple linear regression to examine the impact of external variables on wind speed, and it applies Seasonal Autoregressive Integrated Moving Average (SARIMA) and Holt-Winters Exponential Smoothing (HWES) for wind speed forecasting in these three locations. The hourly and daily interval datasets analysis reveals a weak correlation between external factors and wind speed, with the HWES method identified as the most appropriate approach for modelling and forecasting wind speed, surpassing the SARIMA model by 0.309 RMSE. Forecasting results indicate that a 30-kW wind turbine could supply 8.8 - 35.3% of a small hotel's electricity consumption, depending upon the occupancy rate.